China's Evolving Approach to "Integrated Strategic Deterrence" - Chase, Michael S. (RAND Corporation, 2016)
Drawing on Chinese military writings, this report finds that China's strategic-deterrence concepts are evolving in response to Beijing's changing assessment of its external security environment and a growing emphasis on protecting its emerging interests in space and cyberspace. China also is rapidly closing what was once a substantial gap between the People's Liberation Army's strategic weapons capabilities and its strategic-deterrence concepts.